2016
DOI: 10.1002/bio.3241
|View full text |Cite
|
Sign up to set email alerts
|

Micelle‐enhanced spectrofluorimetric method for quantification of entacapone in tablets and human plasma

Abstract: In this paper, a simple and highly sensitive spectrofluorimetric method was developed and validated for the determination of entacapone (ETC). The proposed method is based on forming a highly fluorescent product through the reduction of ETC with Zn/HCl. The produced fluorophore exhibits strong fluorescence at λ 345 nm after excitation at λ 240 nm. The use of fluorescence enhancers such as Tween-80 and carboxy methyl cellulose (CMC) greatly enhanced the fluorescence of the produced fluorophore by 150% and 200%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is well known that the addition of a surfactant at a concentration above its critical micelle concentration increases its fluorescence quantum yield . This has been used to enhance the fluorescence of many drugs . The spectrophotometric scan of OMG showed λ maximum at 268 nm that was expected to be close to the excitation wavelength while the spectrofluorimetric scan showed overlapped excitation and emission spectra at 263 and 292 nm, respectively (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is well known that the addition of a surfactant at a concentration above its critical micelle concentration increases its fluorescence quantum yield . This has been used to enhance the fluorescence of many drugs . The spectrophotometric scan of OMG showed λ maximum at 268 nm that was expected to be close to the excitation wavelength while the spectrofluorimetric scan showed overlapped excitation and emission spectra at 263 and 292 nm, respectively (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…The aim of our work is to present a new affordable design of experiment (DOE) optimized micelle enhanced spectrofluorimetric method for determination of OMG. The use of surfactants as fluorescence enhancers was reported with spectrofluorimetry for the pharmaceutical analysis of many drugs because of its inherent sensitivity, low cost and easy operation . Moreover, factorial design has been used by analysts for the analytical method development predicting the best parameters by investigating the combined effect of different factors simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey revealed that various methods were reported for the estimation of ETC; including spectrophotometry [5][6], spectrofluorimetry [7], liquid chromatography-tandem mass spectrometry (LC-ESI-MS/ MS) [8][9], Liquid Chromatography with electrochemical detection [10] or UV detection [11] and reversed-phase liquid chromatography with amperometric detection [12].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of the nitro group to an amino group has been utilized previously to retain the fluorescence of some pharmaceutical drugs. [14][15][16] The use of microwell plates can provide a safer and more economical tool for the determination of drug content not only in pharmaceutical dosage forms but also in plasma using microvolumes of samples, therefore decreasing the analysis cost and the risk of human exposure to toxic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Its efficiency enabled it to be used in quality control laboratories. Reduction of the nitro group to an amino group has been utilized previously to retain the fluorescence of some pharmaceutical drugs …”
Section: Introductionmentioning
confidence: 99%